A de novo Non-sense Nuclear Factor I B Mutation (p.Tyr290*) Is Responsible for Brain Malformation and Lung Lobulation Defects - Huang, Hao; Jin, Jieyuan; Wu, Liping; Wu, Huifen; Pi, Huichun; Dong, Yi; Xiang, Rong (Frontiers in Pediatrics, 2022)
Background Nuclear factor I B (NFIB) plays an important role in regulating the transcription of multiple biological processes. Mutations in NFIB cause intellectual disability and macrocephaly. However, studies on abnormal brain and lung development caused by NFIB mutations are lacking. Methods In the present study, we enrolled a fetus with brain malformation and lung lobulation defects from China. Whole-exome sequencing (WES) was performed to detect the candidate genes and Sanger sequencing was performed for mutational analysis. Results After data filtering and bioinformatics prediction, a novel non-sense mutation of NFIB (NM_001190737:c.870C > A;p.Tyr290*) was identified in the fetus. This variant was predicted to produce a truncated NFIB protein because of a premature stop codon and was absent in 200 healthy controls. Conclusion To the best of our knowledge, this is the first case of brain malformation and lung lobulation defects caused by a NFIB variant in Asia. These findings contribute to genetic diagnosis and family counseling and expand our understanding of NFIB mutations as well as brain and lung maturation.